2021
DOI: 10.1002/jpen.2067
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition in Hospitalized Adults With Cerebral Palsy

Abstract: Background: Malnutrition among hospitalized adults with cerebral palsy (CP) has not been extensively explored. We sought to identify impacts of malnutrition on clinical and resource outcomes among hospitalized adults with CP. Methods: This retrospective cohort study surveyed years 2016 and 2017 from the National Inpatient Sample database. Regression models evaluated mortality and resource utilization. Results: 154,219 adults with CP were hospitalized. Among them, 21,064/154,219 (13.5%) had malnutrition. Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Eating dif-Open Journal of Therapy and Rehabilitation ficulties and poor nutritional status occur frequently in patients with CP [23] [24]. One study showed that malnutrition in hospitalized adults with CP is associated with increased mortality [8]. The present study indicates that singing is a useful tool to improve eating ability in adults with CP which potentially could counteract malnutrition.…”
Section: Cp11mentioning
confidence: 54%
See 1 more Smart Citation
“…Eating dif-Open Journal of Therapy and Rehabilitation ficulties and poor nutritional status occur frequently in patients with CP [23] [24]. One study showed that malnutrition in hospitalized adults with CP is associated with increased mortality [8]. The present study indicates that singing is a useful tool to improve eating ability in adults with CP which potentially could counteract malnutrition.…”
Section: Cp11mentioning
confidence: 54%
“…The same study showed that around 35% of the CP individuals were underweight [7]. Malnutrition has not only been detected in children with mild-to-severe CP but also in adults with CP [8]. The nutritional status is worsening with increasing Gross Motor Function Classification System levels (GMFCS levels) both in regards to a higher prevalence and to multimorbidity [9] [10].…”
Section: Introductionmentioning
confidence: 96%
“…The prevalence of underweight was 11.8% and 17.6% among adults with intellectual disability and 0% among adults without intellectual disability 37,60 . The prevalence of malnutrition was 38.3% (95% CI = 7.6%–75.5%; I 2 = 99.5%, p < 0.01; n = 21 294 out of 15 4625; three studies) 59,61,63 . The prevalence of malnutrition was 48.8% among non‐ambulatory adults 59 …”
Section: Resultsmentioning
confidence: 96%
“…37,60 The prevalence of malnutrition was 38.3% (95% CI = 7.6%-75.5%; I 2 = 99.5%, p < 0.01; n = 21 294 out of 15 4625; three studies). 59,61,63 The prevalence of malnutrition was 48.8% among non-ambulatory adults. 59 There was no evidence that the prevalence of obesity was higher in adults with CP than in adults without CP.…”
Section: Nutritional Disordersmentioning
confidence: 99%